2019
DOI: 10.5812/ijcm.91783
|View full text |Cite
|
Sign up to set email alerts
|

Combinational Use of Phytochemicals and Chemotherapeutic Drugs Enhance Their Therapeutic Potential on Human Cervical Cancer Cells

Abstract: Background: The negative side effects of chemotherapeutic drugs have led to the need to identify safer therapeutics. A wide array of epidemiological and experimental data encourages the use of dietary agents to impede or delay different stages of cancer. Well tolerated lower doses of individual agents can be effectively employed if there is therapeutic synergy; thereby minimizing the side effects and enhancing successful outcome. However, a variety of interactions are possible when different agents are used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…In previous studies from our lab, the IC50 value was found to be 1.25 and 5 μM (data published) for topotecan and cisplatin, respectively. 2,50 Similarly, based on our previous studies, the IC50 values of chrysin and luteolin are 15 and 20 μM, respectively. 20,33 The sublethal concentrations were used for these agents based on previous studies at our lab.…”
Section: Cell Culturementioning
confidence: 69%
See 1 more Smart Citation
“…In previous studies from our lab, the IC50 value was found to be 1.25 and 5 μM (data published) for topotecan and cisplatin, respectively. 2,50 Similarly, based on our previous studies, the IC50 values of chrysin and luteolin are 15 and 20 μM, respectively. 20,33 The sublethal concentrations were used for these agents based on previous studies at our lab.…”
Section: Cell Culturementioning
confidence: 69%
“…The experiment was performed in triplicate, and the average is the effect of the drugs in combination and to determine the drug interaction as described in our previous combination study. 2 The formula used to calculate CI is as follows…”
Section: Viability Assaymentioning
confidence: 99%
“…Similarly, binding of EGCG to HDAC4 was found to overlap well with the co-crystallized inhibitors EBE (PDB ID: 6FYZ), TFG (PDB ID: 2VQJ), 9F4 (PDB ID: 4CBT) and HA3 (PDB ID: 2VQM). Suppression of HDACs reverses TSG silencing, lessens growth and induces apoptosis (Sundaram et al 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, currently identified drugs have been shown to be toxic with low specificity. Several studies have demonstrated the anti-cancer effect of dietary bioactive compounds, resulting in apoptosis, transcriptional modulation of molecular targets and potentiation of chemotherapeutic drugs (Kedhari Sundaram et al 2019b;Sundaram et al 2019a). Their anticarcinogenic ability has also been ascribed to their capacity to influence the epigenetic machinery and reestablish TSG transcription (Sundaram et al 2017;Kedhari Sundaram et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in natural compounds such as natural ITCs, which could be used together with conventional chemotherapeutic drugs in combination therapy. It has been reported by many studies that the combinational use of natural ITCs and other anti-cancer agents could achieve synergistic anti-cancer activity [78][79][80][81][82]. In a recent review, Kamal at al.…”
Section: Sfn Prostate Cancermentioning
confidence: 99%